Comparison of the modified ligation of intersphincteric fistula tract (LIFT) with Incision thread drawing method on serum IgA and IL-10 levels in high simple anal fistula - Cai, Qiaoying; Ge, Zhouqin; Zhang, Bo; Gong, Wenjing; admin (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the effect of different techniques on serum immunoglobulin A and interleukin-10 in patients with high simple anal fistula. Method: The cross-sectional study was conducted at Dongyang People’s Hospital, Weishan, China, from January 2019 to April 2021, and comprised patients with high simple anal fistula who were randomly and equally divided into Group A getting treatment with modified ligation of intersphincteric fistula tract, and Group B getting treatment with incision-thread-drawing method. Serum immunoglobulin A and interleukin-10 as well as the Wexner score were compared between the groups. Data was analysed using SPSS 25. Results: Of the 140 patients, there were 70(50%) in each of the two groups. There were 125(89.2%) male subjects overall. The mean age in Group A was 38.91±8.91 years, while in Group B it was 38.20±8.51. Mean hospital stay in Group A was shorter than that in Group B (p<0.001). Mean serum immunoglobulin A and interleukin-10 values were not significantly different at baseline, but on day 7 post-surgery, the difference was significant between the groups (p<0.05). Likewise, Wexner score was significantly different at 3 months post-surgery (p<0.05). There was no significant difference in the incidence of postoperative complications between the groups (p=0.730). Conclusion: The modified ligation of intersphincteric fistula tract method was found to be a better option in the management of patients with high simple anal fistula. Key Words: Modified ligation of intersphincteric fistula tract, LIFT, Incision-thread-drawing method, High simple anal fistula, Immunoglobulin A, IgA, Interleukin 10, IL-10.